2012
DOI: 10.5301/jbm.2011.8737
|View full text |Cite
|
Sign up to set email alerts
|

HPV, KRAS mutations, alcohol consumption and tobacco smoking effects on esophageal squamous-cell carcinoma carcinogenesis

Abstract: Esophageal squamous-cell carcinoma (ESCC) is an invasive neoplastic disease generally associated with poor survival rates. The incidence of ESCC is characterized by marked geographic variation, with highest rates noted in developing Southeastern African, Central and Eastern Asian countries. In the developed Western European and North American regions where there is a low disease incidence, heavy alcohol and cigarette consumption constitute major risk factors. The toxic effects of both these risk factors cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 172 publications
0
30
0
Order By: Relevance
“…In recent years, it has been reported that the rate of OCa from 192,000 in 2005 has increased to 20,000 in 2008 (13,14). Therefore, the presence of HPV infection in the epithelial cell of the ovarian carcinoma has been a marvelous subject (15). Anal, oropharyngeal, penile, vulvar, and HPV-related tumors, represent a further 0.7% of the entire carcinoma regions in both genera (women and men), so that HPV is said to be accountable for 5.2% of the entire carcinoma worldwide (6,16).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been reported that the rate of OCa from 192,000 in 2005 has increased to 20,000 in 2008 (13,14). Therefore, the presence of HPV infection in the epithelial cell of the ovarian carcinoma has been a marvelous subject (15). Anal, oropharyngeal, penile, vulvar, and HPV-related tumors, represent a further 0.7% of the entire carcinoma regions in both genera (women and men), so that HPV is said to be accountable for 5.2% of the entire carcinoma worldwide (6,16).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these enzymes are known to promote DNA synthesis, cell proliferation, invasion, and metastasis [ 27 ]. In this context, resveratrol is known to inhibit de novo synthesis of iNOS and COX2 via inhibition of NF-kB pathway as well the upstream kinases activating this pathway [ 51 ]. Resveratrol also targets nitric oxide production and lipoxygenase-stimulated infl ammatory responses [ 7 ].…”
Section: Resveratrol: As Anti-infl Ammatory Agentmentioning
confidence: 99%
“…Similarly, alcohol has been reported to either directly interacting with cell membrane proteins or modulating cellular function [ 57 ]. Long-term alcohol exposure preferentially causes K -ras mutation, impairs p16INK4A protein expression, and induces mutation in both retinoblastoma (Rb) and p53 proteins thereby, triggering cancer promotion [ 51 ]. Aberration of all these genes promote cell survival, evade apoptosis, and stimulate cell proliferation of cancer cells [ 49 ].…”
Section: Alcohol Interacts With Oncogenes and Tumor Suppressor Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their association with cervical cancer, HPV types are classified as high-risk 18, 31, 33, 35,39,45,51,52,56,58,59,68, 30, 34,53,66,67,69,70,73,82,85) [2]. Evidence of the potential role of HPV in other tumor types has been shown, as well [3][4][5][6][7][8]. High-risk HPV types contribute significantly to viral associated neoplasms, accounting for approximately 600,000 cases (5%) of cancers worldwide annually [9].…”
mentioning
confidence: 99%